Antistatic styrene copolymer for producing carrier tape and preparation method thereof

By synergistically designing a tertiary amine-coupling agent binary carbon black dispersant with a HIPS-PPO alloy, the dispersion problem of high carbon black-filled carrier tape materials was solved, resulting in carrier tape materials with high heat resistance, low resistance, no carbon buildup, and high toughness, meeting the needs of high-speed continuous production.

CN121108670AActive Publication Date: 2025-12-12TIANJIN WAN SU NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202511667960.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2025-12-12
Estimated Expiration
2045-11-14

AI Technical Summary

Technical Problem

Existing technologies cannot simultaneously achieve low surface resistance, high heat resistance, no carbon buildup, no black shedding, and high toughness in carrier materials with high carbon black filling, making it difficult to meet the requirements of high-speed continuous production.

Method used

By employing a synergistic design of a tertiary amine-coupling agent binary carbon black dispersant and a HIPS-PPO heat-resistant alloy, the long-chain alkyl groups of the tertiary amine prevent carbon black particle agglomeration, the coupling agent enhances the interfacial bonding between carbon black and the polymer matrix, and the compatibility of HIPS and PPO is combined to achieve uniform dispersion of conductive carbon black in a styrene matrix.

Benefits of technology

It achieves no crystal points, no carbon buildup, no melting at 225℃ heat sealing, and no black shedding when the tape is torn, with 15%-25% high carbon black filling. It meets the industrial-grade requirements for continuous high-speed production of carrier tapes. The surface resistivity of the material is 105-106Ω, and it has good mechanical properties and processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of antistatic materials, and relates to an antistatic styrene copolymer for producing a carrier tape and a preparation method thereof, and the antistatic styrene copolymer comprises the following components by mass: 45%-60% of HIPS, 6%-10% of HIPS / PPO alloy, 15%-25% of conductive carbon black, 5%-15% of a compatilizer, 6%-15% of a flexibilizer, 2%-5% of a carbon black dispersant, 0.3%-0.8% of an antioxidant, and 0.5%-1% of a lubricant. The carbon black dispersing agent comprises a coupling agent and medium-chain and long-chain aliphatic tertiary amine. Through the collaborative design of the tertiary amine-coupling agent binary carbon black dispersing agent and the HIPS / PPO heat-resistant alloy, the styrene system filled with 15%-25% high carbon black has no crystal point, no carbon deposit, no melting in 225 DEG C heat sealing and no black falling in tape tearing, and the industrial-grade requirement of continuous high-speed production of carrier tapes is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antistatic materials technology, and relates to an antistatic styrene copolymer for producing carrier tapes and its preparation method. Background Technology

[0002] Carrier tape is an indispensable permanent antistatic packaging material for chips and various electronic components. It is a three-layer composite polymer tape product, generally consisting of a middle layer (support layer) and top and bottom surface layers (antistatic layers). It is made into a sheet through a "three-layer co-extrusion" process, and then subjected to secondary thermoforming to a specific shape. The middle layer is usually made of polycarbonate (PC) or acrylonitrile-butadiene-styrene copolymer (ABS). The surface layer and the middle layer (PC / ABS) are antistatic polymer materials with good compatibility, giving the carrier tape permanent antistatic properties and protecting precision electronic components such as chips, capacitors, inductors, and LEDs from electrostatic damage during transportation and storage.

[0003] Carrier tape products undergo instantaneous heat sealing when encapsulating electronic components, requiring the surface material to have high heat resistance and not melt at high temperatures of 180℃-225℃. When unpacking electronic components, the sealing tape should not have any carbon black adhering to it, and it must also meet the requirement that no carbon deposits fall off the extruder head of the production equipment during long-term (8-12 hours) continuous production to avoid the formation of defective products.

[0004] In the prior art, conductive polystyrene systems are widely used as conductive layers in carrier tapes, but they still have the following shortcomings: Chinese patent CN103351564A discloses conductive polystyrene plastic for carrier tapes and its preparation method. Its formulation mainly consists of high-impact polystyrene (HIPS), linear low-density polyethylene (LLDPE), conductive carbon black, white oil, etc. Although it achieves preliminary dispersion of carbon black and basic conductivity, the carbon black content is too high (5%-20%), and there are still problems such as uneven dispersion, easy shedding, and limited heat sealing temperature, which makes it difficult to meet the requirements of high-speed carrier tapes for surface cleanliness and high-temperature heat sealing stability.

[0005] Chinese patent CN103483798A discloses an antistatic PPO / HIPS alloy and its preparation method. The alloy uses a blend of PPO and HIPS and is compounded with antistatic agents such as monoglycerides. It has good mechanical and flame retardant properties, but its antistatic properties depend on small molecule migratory additives, resulting in poor durability. Furthermore, it does not address the dispersion problem of highly filled carbon black systems and is not suitable for carrier materials with high electrostatic conductivity requirements.

[0006] Chinese patent CN106832728A discloses a carbon black / polymer antistatic composite material and its preparation method. The material improves the dispersibility of carbon black by coating it with polyacrylic acid (PAA) and achieves antistatic properties with low carbon black content. However, the carbon black filling amount is limited, and the conductivity is insufficient to meet the low resistivity requirements of high-end carrier tapes. Furthermore, it does not solve the problems of processing thermal stability and carbon black shedding under high filling conditions.

[0007] Chinese patent CN109608808A discloses an antistatic and flame-retardant polystyrene composition, its preparation method and application. The composition achieves flame retardancy and antistatic properties through the compounding of various additives. However, its antistatic agent is a permanent polyoxyethylene type, which is different from the carbon black conductive system. Furthermore, it has not been optimized for dispersion and thermal processing behavior under high carbon black filling, and cannot meet the stringent requirements for carbon black dispersion and heat sealing strength in continuous high-speed molding of carrier tape.

[0008] In summary, existing technologies cannot simultaneously achieve a balance between high carbon black filling, low surface resistivity, high heat resistance, no carbon buildup, no black shedding, and high toughness. A new technical solution is urgently needed to resolve these contradictions. Summary of the Invention

[0009] To overcome the shortcomings of the prior art, this invention provides an antistatic styrene copolymer for producing carrier tapes and its preparation method. It adopts a synergistic design of tertiary amine-coupling agent binary carbon black dispersant and HIPS-PPO heat-resistant alloy, and for the first time achieves the simultaneous achievement of no crystal points, no carbon buildup, no melting at 225℃ heat sealing, and no black shedding when the tape is torn in a styrene system with 15%-25% high carbon black filling, thus meeting the industrial-grade requirements for continuous high-speed production of carrier tapes.

[0010] The technical solution of this invention is: The first aspect of this invention discloses an antistatic styrene copolymer for producing carrier tapes, the formulation of which, by mass percentage, comprises the following components: 45%-60% high-impact polystyrene (HIPS), 6%-10% HIPS / PPO alloy, 15%-25% conductive carbon black (CCB), 5%-15% compatibilizer, 6%-15% toughening agent, 2%-5% carbon black dispersant, 0.3%-0.8% antioxidant, and 0.5%-1% lubricant. The carbon black dispersant comprises a coupling agent and a medium- to long-chain aliphatic tertiary amine, wherein the coupling agent accounts for 0.2%-1.5% of the total mass of the formulation, and the medium- to long-chain aliphatic tertiary amine accounts for 2%-5% of the total mass of the formulation.

[0011] Furthermore, the compatibilizer is one or both of styrene-maleic anhydride copolymer (SMA) and acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH).

[0012] Furthermore, the toughening agent is one or both of styrene-butadiene-styrene block copolymer (SBS) and styrene-ethylene-butene-styrene block copolymer (SEBS).

[0013] Furthermore, the medium- and long-chain aliphatic tertiary amine is selected from one or more of dioctadecylmethyl tertiary amine, dimethyl stearate tertiary amine, and tri-n-dodecylamine, and the coupling agent is a silane coupling agent or a titanate coupling agent.

[0014] Furthermore, the antioxidant is a compound composed of antioxidant 168 and antioxidant 1076 in a mass ratio of 1:2.

[0015] Furthermore, the lubricant is silicone powder or pentaerythritol stearate (PETS).

[0016] Furthermore, its tensile strength is 25 MPa-40 MPa, its flexural strength is 20 MPa-45 MPa, and its cantilever beam notched impact strength is 6 kJ / m. 2 -15kJ / m 2 Its density is 1.01 g / cm³. 3 -1.36g / cm 3 Melt flow rate: 1 g / 10 min - 15 g / 10 min (200 ℃, 5 kg); Surface resistivity: 10 Ω·cm 5 Ω-10 6 Ω.

[0017] A second aspect of this invention discloses a method for preparing the aforementioned antistatic styrene copolymer, comprising the following steps: (1) HIPS and PPO were blended and granulated at a mass ratio of 80:20-90:10 at 250℃-280℃ to obtain HIPS / PPO alloy; (2) The HIPS / PPO alloy, HIPS, conductive carbon black, compatibilizer, toughening agent, carbon black dispersant, antioxidant and lubricant are mixed in proportion, and then mixed and granulated at 220 ℃-250 ℃ to obtain antistatic styrene copolymer.

[0018] The third aspect of the present invention discloses a carrier tape comprising upper and lower surface layers and an intermediate layer, wherein the upper and lower surface layers are made of the aforementioned antistatic styrene copolymer, and the intermediate layer is polycarbonate (PC) or acrylonitrile-butadiene-styrene copolymer (ABS), prepared by a three-layer co-extrusion process.

[0019] The fourth aspect of this invention discloses the application of the aforementioned antistatic styrene copolymer in the preparation of carrier tapes.

[0020] The core technologies of this invention include the dispersion of conductive carbon black and the compatibility and bonding of carbon black with polymer materials, which gives the material high heat resistance and the final product has a surface resistivity of 10. 5 -10 6 Ω has a matte surface, no crystal points, good smoothness, and excellent mechanical properties and processability.

[0021] This invention selects a tertiary amine-coupling agent binary dispersant because: conductive carbon black has a high specific surface area and abundant π electrons, making it highly susceptible to aggregation through strong van der Waals forces and π-π interactions, forming aggregates that cannot provide conductive pathways. The tertiary amine can break up these aggregates and allow the conductive carbon black to be stably distributed in the polymer matrix, thereby forming a highly efficient conductive network. The coupling agent, on the other hand, acts as a "molecular bridge," strengthening the interfacial bonding between the carbon black and the polymer matrix.

[0022] Mechanism of action of tertiary amines: Tertiary amine molecules typically consist of a carbon black-loving, nonpolar long-chain alkyl tail and a polar tertiary amine head group. Anchoring effect of the nonpolar segment: The long-chain alkyl tail of the tertiary amine can strongly adsorb onto the inherently hydrophobic surface of conductive carbon black through hydrophobic interactions and van der Waals forces. This is a spontaneous process because the energy of the system is lower after adsorption.

[0023] Potential role of the head group: The lone pair of electrons on the nitrogen atom of the tertiary amine can weakly interact with a small number of oxygen-containing functional groups (such as carboxyl groups -COOH) on the carbon black surface. The main adsorption force comes from the interaction between the alkyl chain and the graphite crystal facets of the carbon black. After adsorption, the tertiary amine mainly prevents the carbon black particles from re-agglomerating in the following ways: When tertiary amine molecules are densely adsorbed onto the surface of carbon black particles, their outwardly extending long-chain alkyl groups form a protective layer of "polymer chain" with a certain thickness and strength. When two carbon black particles coated with tertiary amine approach each other, these extended alkyl chains begin to compress and overlap. This leads to two unfavorable entropy reduction processes: (1) the degree of freedom of chain segment movement decreases (conformational entropy decreases); (2) solvent molecules between chains are squeezed out (dilution entropy decreases). According to the second law of thermodynamics, this entropy reduction process is non-spontaneous. Therefore, an effective repulsive force is generated between the particles, preventing them from approaching and agglomerating further. This is the most core and effective stabilizing mechanism of tertiary amines as dispersants.

[0024] This invention uses a HIPS / PPO alloy (HIPS:PPO mass ratio 80:20-90:10). Due to the high melting point of PPO (280 ℃), it needs to be blended and granulated using a twin-screw extruder at 250 ℃-280 ℃. Both HIPS and PPO molecules contain benzene rings and other structural units, thus exhibiting a certain degree of compatibility. Both molecules contain a large number of benzene rings, which can generate strong π-π conjugated interactions. This intermolecular force is far stronger than ordinary van der Waals forces, essentially forming countless "tiny hands" between the two molecular chains, tightly binding them together.

[0025] Secondly, the solubility of these two resins is very close: PPO has a solubility of 19, and HIPS has a solubility of 18.6. The difference between them is very small (generally, Δδ < 0.5 (J / cm³)^1 / 2 is considered to indicate good compatibility), indicating that PPO and HIPS have a strong thermodynamic tendency to spontaneously mix. This means that during melt blending, the two polymer chains can diffuse into each other, eventually forming a homogeneous structure at the microscale (molecular chain level). The strength of this interaction is even sufficient to overcome the strong interchain interactions of the PPO molecular chains themselves, allowing them to be "diluted" and "isolated" by the HIPS molecular chains, ultimately forming a compatible homogeneous system.

[0026] The advantages and beneficial effects of this invention are: (1) The synergistic design of the tertiary amine-coupling agent binary dispersant and HIPS-PPO heat-resistant alloy solved the dispersion problem of 15%-25% high-content conductive carbon black in a styrene matrix. The long-chain alkyl group of the tertiary amine effectively prevents the re-agglomeration of carbon black particles through steric hindrance, while the coupling agent acts as a "molecular bridge" to strengthen the interfacial bonding between carbon black and the polymer matrix. This synergistic design ensures that carbon black is stably and uniformly dispersed at the scale of primary aggregates from both thermodynamic and kinetic perspectives, fundamentally eliminating crystal point defects caused by carbon black agglomeration, and avoiding carbon deposition caused by carbon black retention and decomposition during processing.

[0027] (2) Taking advantage of the similar solubility parameters of HIPS and PPO and the strong π-π conjugated interaction generated by the benzene ring structure, a HIPS / PPO alloy was prepared in advance. This alloy not only significantly improves the heat resistance of the material to meet the industrial-grade requirement of not melting in the 225℃ heat sealing process, but also ensures that the material still has good melt flowability and processability in the relatively low processing window of 220-250℃ due to the good compatibility of the two.

[0028] In summary, the prepared styrene copolymer is free of crystal points and carbon deposits, does not melt when heat-sealed at 225 ℃, and does not shed black residue when torn, meeting the industrial-grade requirements for continuous high-speed production of carrier tapes. Detailed Implementation

[0029] The present invention will be further described in detail below through specific embodiments. The following embodiments are merely descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.

[0030] High-impact polystyrene (HIPS): Shanghai SECCO Petrochemical Co., Ltd., resin grade 622; or Dushanzi Petrochemical Co., Ltd., HIE-1.

[0031] Conductive carbon black: Cabot Chemicals (Tianjin) Co., Ltd., grade BP2000. Or Tianjin Baochi Chemical Technology Co., Ltd., BC-90.

[0032] PPO: Ruicheng Lanxing Chemical Co., Ltd., LXR040.

[0033] Styrene-maleic anhydride copolymer (SMA) Jiaxing Huawen Chemical Co., Ltd., SMA-700.

[0034] Acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH), Shenyang Ketong Plastics Co., Ltd., KT-2.

[0035] Styrene-butadiene-styrene (SBS): Yueyang Baling Petrochemical Co., Ltd., YH-792.

[0036] Silane coupling agent: Anhui Boiling Point New Materials Co., Ltd., FD-550A.

[0037] Titanate coupling agent: Anhui Boiling Point New Materials Co., Ltd., FD-201.

[0038] Dioctadecylmethyl tertiary amine: Nantong Zhonghe Chemical Co., Ltd.

[0039] Dimethyl stearate: Wuhan Jiyesheng Chemical Co., Ltd.

[0040] Antioxidant 168: Anhui Xinxiu Chemical Co., Ltd.

[0041] Antioxidant 1076: Tianjin Lianlong New Materials Co., Ltd.

[0042] Silicone powder: Chengdu Silike Technology Co., Ltd., S-201.

[0043] Pentaerythritol stearate (PETS): Qingdao Sainuo New Materials Co., Ltd., 603.

[0044] Example 1 An antistatic styrene copolymer for producing carrier tapes, comprising the following components by weight percentage: High-impact polystyrene (HIPS) 57.5%; Conductive carbon black (CCB) 18%, HIPS / PPO alloy 6%; Compatibilizers: 3% styrene-maleic anhydride copolymer (SMA), 5% maleic anhydride-grafted acrylonitrile-butadiene-styrene copolymer (ABS-g-MAH); Toughening agent: 6% styrene-butadiene-styrene block copolymer (SBS); Carbon black dispersant: 0.5% silane coupling agent, 3% dioctadecylmethyl tertiary amine; Antioxidant: 0.3% of a compound of antioxidant 168 and antioxidant 1076 in a 1:2 mass ratio; Lubricant: 0.7% silicone powder.

[0045] The preparation method includes the following steps: (1) HIPS and PPO were blended and granulated at 260°C at a mass ratio of 80:20 to obtain HIPS / PPO alloy; (2) HIPS / PPO alloy, HIPS, conductive carbon black, compatibilizer, toughening agent, carbon black dispersant, antioxidant and lubricant are mixed in proportion, and then mixed and granulated at 240 °C to obtain antistatic styrene copolymer.

[0046] Example 2 The only difference from Example 1 is that, by mass percentage, it includes the following components: High-impact polystyrene (HIPS) 48.7%; Conductive carbon black (CCB) 22%; HIPS / PPO alloy 6%; Compatibilizers: 5% styrene-maleic anhydride copolymer (SMA), 6% acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH). Toughening agent: 6% styrene-butadiene-styrene block copolymer (SBS), Carbon black dispersant: titanate coupling agent 0.8%, dimethyl tertiary amine stearate 4%. Antioxidant: 0.5% of a compound of antioxidant 168 and antioxidant 1076 in a 1:2 mass ratio. Lubricant: Pentaerythritol stearate (PETS) 1%.

[0047] Comparative Example 1 (without tertiary amines) The only difference from Example 1 is that, by weight percentage, it includes the following components: 57.5% high-impact polystyrene (HIPS), 18% conductive carbon black (CCB), 6% HIPS / PPO alloy, 3% styrene-maleic anhydride copolymer (SMA), 5% acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH), 6% styrene-butadiene-styrene (SBS), 3.5% silane coupling agent, 0.3% antioxidant (a blend of antioxidant 168 and antioxidant 1076 in a 1:2 weight ratio), and 0.7% silicone powder.

[0048] Comparative Example 2 (without coupling agent) The only difference from Example 1 is that, by weight percentage, it includes the following components: High-impact polystyrene (HIPS): 64.5%, conductive carbon black (CCB) 18%, HIPS / PPO alloy 5%, styrene-maleic anhydride copolymer (SMA) 3%, acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH) 5%, dioctadecylmethyl tertiary amine 3.5%, antioxidant (a compound of antioxidant 168 and antioxidant 1076 in a 1:2 weight ratio) 0.3%, and silicone powder 0.7%.

[0049] Comparative Example 3 (without HIPS / PPO alloy) The only difference from Example 1 is that, by weight percentage, it includes the following components: 63.5% high-impact polystyrene (HIPS), 18% conductive carbon black (CCB), 3% styrene-maleic anhydride copolymer (SMA), 5% acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH), 6% styrene-butadiene-styrene (SBS), 0.5% silane coupling agent, 3% dioctadecylmethyl tertiary amine, 0.3% antioxidant (a blend of antioxidant 168 and antioxidant 1076 in a 1:2 weight ratio), and 0.7% silicone powder.

[0050] Comparative Example 4 (Conventional Dispersant) The only difference from Example 1 is that, by weight percentage, it includes the following components: 58.5% high-impact polystyrene (HIPS), 18% conductive carbon black (CCB), 5% HIPS / PPO alloy, 3% styrene-maleic anhydride copolymer (SMA), 5% acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH), 8% styrene-butadiene-styrene (SBS), 1.5% ethylene bis-stearamide (EBS), 0.3% antioxidant (a blend of antioxidant 168 and antioxidant 1076 in a 1:2 weight ratio), and 0.7% silicone powder.

[0051] Comparative Example 5 (Low Carbon Black) The only difference from Example 1 is that, by weight percentage, it includes the following components: 64.5% high-impact polystyrene (HIPS), 12% conductive carbon black (CCB), 5% HIPS / PPO alloy, 3% styrene-maleic anhydride copolymer (SMA), 5% acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH), 6% styrene-butadiene-styrene (SBS), 0.5% silane coupling agent, 3% dioctadecylmethyl tertiary amine, 0.3% antioxidant (a compound of antioxidant 168 and antioxidant 1076 in a 1:2 mass ratio), and 0.7% silicone powder.

[0052] Comparative Example 6 The only difference from Example 1 is that PPO is added separately and not made into a HIPS / PPO alloy.

[0053] By weight percentage, it includes the following components: 61% high-impact polystyrene (HIPS), 18% conductive carbon black (CCB), 2.5% PPO, 3% styrene-maleic anhydride copolymer (SMA), 5% acrylonitrile-butadiene-styrene grafted maleic anhydride copolymer (ABS-g-MAH), 6% styrene-butadiene-styrene (SBS), 0.5% silane coupling agent, 3% dioctadecylmethyl tertiary amine, 0.3% antioxidant (a blend of antioxidant 168 and antioxidant 1076), and 0.7% silicone powder.

[0054] Performance tests were conducted on the antistatic styrene copolymers of the examples and comparative examples: Mechanical properties include tensile strength (GB / T-1040-2018), flexural strength (GB / T 9341-2008), notched impact strength of cantilever beam (GB / T 1843-2008), and density (GB / T 1033-2018).

[0055] During production, it is necessary to control the melt flow rate within a reasonable range. Since it is a three-layer co-extrusion process, the melt flow rate of the antistatic surface layer needs to match that of the intermediate layer (PC or ABS); otherwise, it will affect the extrusion molding. Excessive or insufficient flow rate of the surface layer will result in over-coating or uneven coating, affecting product quality. The melt flow rate test method refers to GB / T 3683-2000, and the surface resistivity test method refers to GB / T 1410-2006.

[0056] The surface crystal points, mold opening carbon deposits, and heat sealing blackening were observed using the adhesive tape peeling method, as shown in Table 1.

[0057] Table 1

[0058] As shown in Table 1, the tensile strength of the antistatic styrene copolymer in the examples is 25 MPa-40 MPa, the flexural strength is 20 MPa-45 MPa, and the notched cantilever beam impact strength is 6 kJ / m. 2 -15kJ / m 2 Density: 1.01 g / cm³ 3 -1.36g / cm 3 Melt flow rate of 5kg at 200℃: 1g / 10min-15g / 10min, surface resistivity: 10 5 Ω -10 6 Ω.

[0059] In Comparative Example 1, without tertiary amine dispersant, the conductive carbon black dispersion was not ideal, and a small number of crystal points appeared on the surface of the carrier tape, with an average of about 1 small crystal point per meter.

[0060] In Comparative Example 2, without coupling agent, carbon deposits increased.

[0061] In Comparative Example 3, without HIPS / PPO alloy, resin residue and black residue appeared on the surface of the heat sealing die during heat sealing of the carrier tape with film coating.

[0062] Comparative Example 4 showed that conventional dispersants such as ethylene bis-stearamide (EBS) and polyethylene wax had a weak dispersing effect on conductive carbon black, mainly due to poor effect on the mutual adsorption and aggregation of surface charges of conductive carbon black. This resulted in more crystal points appearing on the carrier surface, increased carbon deposition, and failure to meet the requirement of no crystal points in the product.

[0063] Comparative Example 5: Low levels of conductive carbon black are beneficial for dispersion, but reduce the conductivity of the carrier (surface resistivity 10). 11 The Ω value decreases accordingly, failing to meet the product's antistatic requirements.

[0064] Adding PPO alone in Comparative Example 6, without forming an HIPS / PPO alloy, results in a large difference in processing temperature between PPO resin (around 280℃) and HIPS resin (around 180℃) in the mixing process. In a system where HIPS is the main resin, this leads to a weakening of the screw shearing effect during mixing, affecting the dispersion of conductive carbon black and resulting in a small number of crystal points.

[0065] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the inventive concept, and these all fall within the protection scope of the present invention.

Claims

1. An antistatic styrene copolymer for producing carrier tapes, characterized in that, The formulation comprises the following components by mass percentage: HIPS 45%-60%, HIPS / PPO alloy 6%-10%, conductive carbon black 15%-25%, compatibilizer 5%-15%, toughening agent 6%-15%, carbon black dispersant 2%-5%, antioxidant 0.3%-0.8%, and lubricant 0.5%-1%. The carbon black dispersant includes coupling agent and medium- and long-chain aliphatic tertiary amines, wherein the coupling agent accounts for 0.2%-1.5% of the total mass of the formulation, and the medium- and long-chain aliphatic tertiary amines account for 2%-5% of the total mass of the formulation.

2. The antistatic styrene copolymer according to claim 1, characterized in that, The compatibilizer is one or both of styrene-maleic anhydride copolymer and acrylonitrile-butadiene-styrene-grafted maleic anhydride copolymer.

3. The antistatic styrene copolymer according to claim 1, characterized in that, The toughening agent is one or both of styrene-butadiene-styrene block copolymer and styrene-ethylene-butene-styrene block copolymer.

4. The antistatic styrene copolymer according to claim 1, characterized in that, The medium- and long-chain aliphatic tertiary amine is selected from one or more of dioctadecylmethyl tertiary amine, dimethyl stearate tertiary amine, and tri-n-dodecylamine, and the coupling agent is a silane coupling agent or a titanate coupling agent.

5. The antistatic styrene copolymer according to claim 1, characterized in that, The antioxidant is a compound composed of antioxidant 168 and antioxidant 1076 in a mass ratio of 1:

2.

6. The antistatic styrene copolymer according to claim 1, characterized in that, The lubricant is silicone powder or pentaerythritol stearate.

7. The antistatic styrene copolymer according to claim 1, characterized in that, Its tensile strength is 25MPa-40MPa, its flexural strength is 20MPa-45MPa, and its cantilever beam notched impact strength is 6 kJ / m. 2 -15kJ / m 2 Its density is 1.01 g / cm³. 3 -1.36g / cm 3 At 200 ℃, the melt flow rate of 5 kg is 1 g / 10 min to 15 g / 10 min, and the surface resistivity is 10. 5 Ω-10 6 Ω.

8. A method for preparing an antistatic styrene copolymer as described in any one of claims 1-7, characterized in that, Includes the following steps: (1) HIPS and PPO were blended and granulated at a mass ratio of 80:20-90:10 at 250℃-280℃ to obtain HIPS / PPO alloy; (2) The HIPS / PPO alloy, HIPS, conductive carbon black, compatibilizer, toughening agent, carbon black dispersant, antioxidant and lubricant are mixed in proportion, and then mixed and granulated at 220 ℃-250 ℃ to obtain antistatic styrene copolymer.

9. A carrier tape comprising upper and lower surface layers and an intermediate layer, characterized in that, The upper and lower surface layers are made of the antistatic styrene copolymer as described in any one of claims 1-7, and the middle layer is polycarbonate or acrylonitrile-butadiene-styrene copolymer, prepared by a three-layer co-extrusion process.

10. The use of the antistatic styrene copolymer as described in any one of claims 1-7 in the preparation of carrier tapes.

Citation Information

Patent Citations

  • Antistatic PPO (Poly-p-Phenylene Oxide) / HIPS (High Impact Polystyrene) alloy and preparation method thereof

    CN103483798A

  • Carbon black / polymer antistatic composite material and preparation method thereof

    CN106832728A

  • Antistatic and flame-retardant polystyrene composition as well as preparation method and application thereof

    CN109608808A

  • Electric conduction polystyrene plastic for carrier tape, and preparation method thereof

    CN103351564A

  • Alloy antistatic material for wafer trays, and preparation method thereof

    CN109251507A

Cited By

  • HIPS (High Impact Polystyrene) modified composite material as well as preparation method and application thereof

    CN121930609A